First record of a mermithid nematode (Nematoda: Mermithidae) parasitizing winged females of gall‐forming aphids (Hemiptera: Aphididae: Eriosomatinae). Issue 4 (11th August 2021) - Tong, Xin; Kanzaki, Natsumi; Akimoto, Shin‐ichi
Abstract: Juvenile mermithid nematodes were found to parasitize winged females (sexuparae) of Eriosoma auratum and Tetraneura radicicola . The morphological characteristics of mermithid nematodes are briefly described. The 18S rDNA and 28S rDNA obtained from one nematode were sequenced and used to construct a Bayesian phylogenetic tree, on which the host ranges of mermithid nematodes were represented. Our study indicated that mermithid parasitism of sexuparae led to fewer and smaller sexual female embryos. This is the first record of a mermithid in relation to eriosomatine aphids and the fourth record with respect to Aphididae. Abstract : This is the first report of a mermithid nematode (Nematoda: Mermithidae) parasitizing winged females (sexuparae) of gall‐forming aphids (Hemiptera: Aphididae: Eriosomatinae). Our study indicated that mermithid parasitism of sexuparae led to fewer and smaller sexual female embryos. Further, molecular phylogeny with host ranges was also constructed in this paper to show the association between mermithid nematodes and their host species. This is the first record of a mermithid in relation to eriosomatine aphids and the fourth record with respect to Aphididae.